INFLUENCE OF THE SILICON INTERLAYER ON DIAMOND-LIKE CARBON FILMS DEPOSITED ON GLASS SUBSTRATES - Deiler Antonio Lima Oliveira; Evaldo José Corat; Vladimir Jesus Trava-Airoldi; Anderson Oliveira Lobo; Fernanda Roberta Marciano (Revista UniVap, 2012)
Diamond-like carbon (DLC) films as a hard protective coating have achieved great success in a diversity of technological applications. However, adhesion of DLC films to substrates can restrict their applications. The influence of a silicon interlayer in order to improve DLC adhesion on glass substrates was investigated. Amorphous silicon interlayer and DLC films were deposited using plasma enhanced chemical vapor deposition from silane and methane, respectively. The bonding structure, transmittance, refraction index, and adherence of the films were also evaluated regarding the thickness of the silicon interlayer. Raman scattering spectroscopy did not show any substantial difference in DLC structure due to the interlayer thickness of the silicon. Optical measurements showed a sharp decrease of transmittance in the ultra-violet region caused by the fundamental absorption of the light. In addition, the absorption edge of transmittance shifted toward longer wavelength side in the ultra-violet region as the thickness of the silicon interlayer increased. The tribological results showed an increase of DLC adherence as the silicon interlayer increased, which was characterized by less cracks around the grooves.